Recognizing a MIS-Chievous Cause of Acute Viral Gastroenteritis - Josyabhatla, Rohit; Kamdar, Ankur A.; Armbrister, Shabba A.; Daniel, Rhea; Boukas, Konstantinos; Smith, Keely G.; Van Arsdall, Melissa R.; Kakarala, Kokila; Flores, Anthony R.; Wanger, Audrey; Liu, Yuying; Rhoads, Jon Marc (Frontiers in Pediatrics, 2021)
Historically, children evaluated for vomiting and diarrhea secondary to viral enteritis have symptoms lasting 2-4 days and respond to supportive care, including oral rehydration and anti-emetics if required. Recently, within a 14-day timespan, we encountered 3 children with severe diarrhea who rapidly became dehydrated and went into hypotensive shock. Although SARS-CoV-2 molecular tests were negative by nasopharyngeal swab, all were later found to have MIS-C. This small case series underscores features reported in previous larger studies and emphasizes the rapid clinical evolution of this condition. We highlight the importance of early recognition of cardinal laboratory findings characteristic of MIS-C (i.e., lymphopenia, markedly elevated acute phase reactants, and hypoalbuminemia). We also show serologic evidence that the pathophysiological mechanism of SARS-CoV-2 related diarrhea may differ from other causes of dehydrating vomiting and diarrhea, with no serologic evidence of villus cell injury.